2017
DOI: 10.1007/s11060-016-2349-9
|View full text |Cite|
|
Sign up to set email alerts
|

The role of histone modifications and telomere alterations in the pathogenesis of diffuse gliomas in adults and children

Abstract: Genetic profiling is an increasingly useful tool for sub-classification of gliomas in adults and children. Specific gene mutations, structural rearrangements, DNA methylation patterns, and gene expression profiles are now recognized to define molecular subgroups of gliomas that arise in distinct anatomic locations and patient age groups, and also provide a better prediction of clinical outcomes for glioma patients compared to histologic assessment alone. Understanding the role of these distinctive genetic alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 77 publications
(154 reference statements)
1
22
0
Order By: Relevance
“…H3F3A/ATRX-DAXX/TP53 mutations are strongly associated with alternative lengthening of telomeres, a telomerase-independent telomere maintenance mechanism that could allow unlimited cellular proliferation in pediatric glioblastoma (13, 33, 37, 38). …”
Section: Histone Methylation In Pediatric Gliomamentioning
confidence: 99%
“…H3F3A/ATRX-DAXX/TP53 mutations are strongly associated with alternative lengthening of telomeres, a telomerase-independent telomere maintenance mechanism that could allow unlimited cellular proliferation in pediatric glioblastoma (13, 33, 37, 38). …”
Section: Histone Methylation In Pediatric Gliomamentioning
confidence: 99%
“…Contrary to adult IDH-wildtype diffuse glioma, H3-mutant malignant pediatric glioma frequently demonstrate ALT [185], and several studies reported frequent co-occurrence of ATRX mutations in both H3 K27 and G34 mutant gliomas. However, reports of co-occurrence vary between 30% and 60% for K27 and 75% to 100% for G34, suggesting that there is a role for telomerase in many of these tumors as well [186].…”
Section: A Model For the Temporal Molecular Pathogenesis Of Gliomasmentioning
confidence: 99%
“…The results from this work fit within a broader literature that has demonstrated the oncogenic properties of H3K27 mutations in diffuse midline gliomas. [6][7][8] In these tumors, the H3K27M mutation also results in global loss of H3K27 methylation levels. Given the importance of chromatin structure in transcription factor binding, several questions remain to define how H3K27 mutations and lower K27me levels cooperate with RUNX1 mutations: where are the mutant histones located in relation to RUNX1 binding sites?…”
mentioning
confidence: 99%
“…5 The hyperhemolysis paradigm (HHP), through which it is hypothesized that chronic hemolysis in SCD sequentially causes increased cell-free plasma hemoglobin, nitric oxide biodeficiency, endothelial dysfunction, pulmonary hypertension, and vascular complications, led to the concept of 2 different subphenotypes of SCD: one characterized by the constellation of high hemoglobin levels, vaso-occlusive pain crises, acute chest syndrome, and osteonecrosis and the other by hemolysis, pulmonary hypertension, priapism, leg ulcers, and stroke (see figure). 6,7 The controversy involves both the concept that there might be a clear divide between these 2 subphenotypes and the extent of the overlap between them. Furthermore, studies supporting the HHP have mostly been conducted in the United States, and to date, its appraisal in the context of SCD in Africa has been extremely limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation